H-2 linkage control of resistance to subcutaneous infection with Mycobacterium lepraemurium. - Curtis, J (1982)
The H-2 linkage of the gene or genes controlling resistance to subcutaneous infection with 10(7) Mycobacterium lepraemurium organisms was investigated by using H-2 congenic strains on BALB and B10 backgrounds. Resistance was assessed by counting the organisms present at the infection site in the footpad and in the draining (right popliteal) lymph node 20 weeks after infection. When mice of BALB and B10 backgrounds with the same H-2 haplotype were compared, the BALB mice were always more susceptible. However, BALB/K (H-2k) mice were more susceptible than BALB/B (H-2b) mice, and BALB/B mice were more susceptible than BALB/c (H-2d) mice. There was no detectable difference in the resistance of B10.D2/n (H-2d) mice and B10 (H-2b) mice, but B10.BR (H-2k) mice were more susceptible than mice of the other two B10 strains. BALB/K was the only strain in which a high proportion of mice showed significant dissemination of organisms to the liver and spleen.